Segmentation of Mammography Images Enhanced by Histogram Equalization - Sahakyan, Armen (Mathematical Problems of Computer Science, 2021)
The mammography is the most effective procedure for an early diagnosis of the breast cancer. In this paper, a technique for detecting masses in mammographic images will be presented. Image enhancement techniques, based on histogram equalization, are shown and used before image segmentation. Threshold technique is proposed for an image segmentation which is a very critical task in any image processing. Enhancement methods are implemented on a mammogram and accordingly, a comparison between the methods for better threshold is carried out.